Combination of β-mannanase plus multi-carbohydrase complex in simple or complex post-weaned pig diets on nutrient metabolism and gut health - Galli, Gabriela M.; Andretta, Ines; Carvalho, Camila L.; Stefanello, Thais B.; Mendéz, Maria S. C.; Mendes, Ricardo E.; Horn, Vitor W.; Kipper, Marcos (Frontiers in Veterinary Science, 2024)
This study was conducted to evaluate whether adding β-mannanase alone or in combination with a multi-carbohydrase complex to simple and complex diets could improve diet digestibility, nutrient and energy metabolism, and gut health in weaned pigs. Thirty pigs (7.9 kg ± 0.851 kg) weaned at 28 days were randomly split into a 2 × 3 factorial arrangement, considering a simple (corn and soybean meal-based diet) or complex diet (13% point reduction in inclusion of soybean meal, 5% of whey power, and 2.5% of spray-dried plasma compared to the simple diet) and diet without any addition (control) or the addition of β-mannanase (BM; 0.300 g/kg of the diet) or β-mannanase plus a multi-carbohydrase complex blend such as xylanase, β-glucanase, and arabinofuranosidases (BM + MCC; 0.300 + 0.050 g/kg of the diet) for 17 days post-weaned. Total fecal and urine samples were collected on days 11–17. Fecal samples were collected from all pigs to identify fecal biomarkers using commercial ELISA tests. Blood samples were collected from all pigs at the end of the experimental period to assess serum concentrations of acute-phase proteins. All pigs were euthanized on day 18 for intestinal tissue collection. The simple diet had greater (p < 0.05) protein digestibility and metabolizability coefficients than the complex diet. Greater (p < 0.05) energy digestibility and energy metabolizability coefficients were observed in the BM and BM+ MCC compared to the control diet. On average, BM improved by 64 kcal/kg and BM + MCC improved by 100 kcal/kg of metabolizable energy. Furthermore, the addition of BM and BM + MCC to the diets led to lower fecal moisture and fecal output. Moreover, the BM and BM + MCC diets also reduced fecal calprotectin concentrations by 29 and 46%, respectively, compared to control pigs (p < 0.001). We conclude that simple diets are a suitable alternative to complex diets, without compromising the nutrient digestibility and gut health of post-weaned pigs. The addition of exogenous enzymes improves nutrient and energy utilization, as well as the absorption area, and decreases calprotectin concentrations.